Uso de la tecnología móvil y su relación con el desarrollo de habilidades sociales en escolares - Borjas Aldamas, Lucero (2019)
The present work of quantitative research, descriptive correlational cross-section, aimed to determine the relationship between the use of mobile technology and the development of social skills in schoolchildren of an educational institution “Nuestra Señora de Guadalupe”. The sample universe consisted of 60 school children from the fifth grade of primary school who met the inclusion criteria. For the collection of data, two instruments were used: Test of the level of use of mobile technology and test of the level of development of social skills for school children. The information was obtained and processed in the SPSS 25.0 for Windows and analyzed by the statistical test "Chi - square". After the analysis, the following conclusions were reached: The level of use of mobile technology in 5th grade primary school students is 71.7 percent low, 23.3 percent moderate and only 5 percent high. The development of social skills is high (56.7 percent) and high (36.7 percent) and only 6.7 percent is average. The relationship between the level of use of mobile technology and the development of social skills is highly significant, evidenced by the Chi square test whose value is p = 0.000 <0.05